POTENSI ISOLAT BAKTERI ASAM LAKTAT DARI ILEUM GALLUS GALLUS SEBAGAI PROBIOTIK PAKAN FERMENTASI UNGGAS - Nasution, Maulida Putri; Pradana, Tengku Gilang; Rusdhi, Alfath; Siswoyo, Purwo; Putra, Andhika; Negara, Adhona Bhajana Wijaya (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
This study aims to determine the potential of lactic acid bacteria from ileum Gallus gallus as a probiotic for fermented poultry feed. This research was carried out at the Laboratory of Experimental Gardens and Livestock (LKPP) of Panca Budi Development University. Research methods include tests of gastric acid resistance and resistance to bile salts. The results showed that there were three isolates of lactic acid bacteria that were resistant to stomach acid pH, namely P2, P7 and P8 isolates while three isolates that were resistant to bile salts, namely P2, P3, P5, P7, P8 and P9 isolates. The three isolates of lactic acid bacteria, namely P2, P7 and P8 have resistance to the pH of stomach acid and bile salts so that they have the potential to be formulated as probiotics for fermented poultry feed.